Green Accounting, Corporate Governance, Sustainable Development: The Moderating Effect of Corporate Social Responsibility - Wati, Yenny; Chandra, Teddy; Irman, Mimelientesa; Rahman, Sarli (The Indonesian Journal of Accounting Research, 2024)
Sustainability is essential to explore since it includes economic, environmental, and social consequences, as well as positive and negative implications on Indonesia's sustainable development aims. This study aimed to explore the impact of green accounting and corporate governance on sustainable development. In the present research, researchers employed corporate social responsibility as a moderating variable to analyze the independent variable on sustainable development. The model was created and evaluated utilizing 768 observation data from 146 manufacturing businesses listed on IDX (Indonesia Stock Exchange) between 2017 and 2022. The partial least squares approach was used to investigate moderating variables. According to the findings, green accounting and corporate governance (board of commissioners, board of directors, audit committee) positively impact sustainable development. Corporate social responsibility can act as a moderating variable, increasing the impact of green accounting and corporate governance on sustainable development. Our study contributes empirical evidence to the body of knowledge about sustainable development, allowing the public to comprehend the role of businesses in it better. Companies can concentrate on social responsibilities that improve a country's or firm's competitiveness. The study's findings can help influence the adoption of corporate social responsibility policies.